A Simple Spectrophotometric Determination of Cyanides by P-nitrobenzaldehyde and Tetrazolium Blue (Advances in Military Technology, 2022)
The article describes a simple and a very sensitive spectrophotometric method for determining free cyanides, based on their catalytic reaction with p-nitrobenzaldehyde. Cyanide ions allow for a transformation of p-nitrobenzaldehyde into its transitory reactive cyanohydrin, which reduces a redox indicator, the tetrazolium blue, into a purple-coloured diformazan derivative. The product’s absorption maximum is 520 nm, the determination limit found by calculation is 0.005 mg·l–1 and molar absorptivity is 4.86 × 105 l·mol–1·cm–1. Determination is obstructed by the presence of strong reductive substances.